Literature Review on Innovative Leadership of Principals in the Era of Disruption in School Management - Hastuti, Tri Maria; Nismara, Widyadhana Benda S.; Nugroho, Leyvisca Kristi; Asyam, Muhamad Syafiq; Setiawan, Leonardus Robertino Juan (Jurnal Inovasi Pembelajaran Karakter, 2025)
The era of disruption characterized by technological advances and rapid social change requires school principals to not only carry out administrative functions but also appear as innovative agents of change in leading educational institutions. The importance of creative leadership in facing the challenges of the Industrial Revolution 4.0 and Society 5.0 directly impacts the school management system. This study analyzes the roles, strategies, challenges, and solutions of school principals' innovative leadership in the era of disruption in education management. This research uses a descriptive qualitative method through a literature review approach by examining various sources of relevant academic literature. The results showed that innovative leadership can improve the effectiveness of school management through an adaptive, collaborative, and technology-based approach. Principals with managerial, transformational, and digital competencies can encourage sustainable improvement in the quality of education. This study is helpful as a theoretical contribution to the development of principal leadership models relevant to the times' demands and a reference for policymakers and education practitioners in strengthening a resilient and competitive school management system in the era of disruption.